(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Studies done on severe COVID-19 have revealed a wide heterogeneity in intensive care clinical outcomes across various countries. We aimed to identify the demographic features and outcomes of mechanically ventilated COVID-19 patients with respiratory failure in Pakistan in resource limited settings. Methods: This was a cross-sectional study conducted at the COVID-19 Intensive care unit (ICU) of Jinnah postgraduate medical center in Karachi, Pakistan. 86 patients who received mechanical ventilation in a period of five months from 1/2/2021 till 30/6/2021 were included in the study. Patient demographic characteristics, comorbidities, clinical manifestations of COVID-19 infection, laboratory values at the time of presentation (hemoglobin, Neutrophil lymphocyte ratio, platelets, glomerular filtration rate, C-reactive protein, D-dimers, Ferritin, liver function tests and electrolytes) and mode and duration of ventilation, final outcome (survivor vs. non-survivor) and cause of death in non-survivors were recorded. Results: 86 patients, who required mechanical ventilation because of severe respiratory distress not alleviated by non-invasive methods of ventilation, were included in the study. 66.3% (n=57) were males and 33.7% (n=29) were females. Mean age was 59 (SD 12). The most common comorbidities were diabetes mellitus and hypertension 44.2% (n=38) each. Only 3 (3.4%) of mechanically ventilated patients were extubated and 1 patient was eventually discharged home on room air. The mortality rate was 98.8% and only one patient survived. The most common causes of death were respiratory failure (86%, n=74), renal failure (48.8%, n=42) and sepsis (18.6%, n=16). Conclusion: Mortality in COVID-19 patients who require mechanical ventilation is very high in resource limited settings because of the lack of essential medications, specialized teams and established protocols of ICU management and is not related to the demographic characteristics and comorbidities of patients and severity of disease at presentation. Keywords: COVID-19, Intensive Care Unit, Mechanical Ventilation, Mortality